2014
DOI: 10.1177/0022034514520708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Life-long Fluoride Intake on Bone Measures of Adolescents

Abstract: Controversy persists concerning the impact of community water fluoridation on bone health in adults, and few studies have assessed relationships with bone at younger ages. Ecological studies of fluoride's effects showed some increase in bone mineral density of adolescents and young adults in areas with fluoridated water compared with non-fluoridated areas. However, none had individual fluoride exposure measures. To avoid ecological fallacy and reduce bias, we assessed associations of average daily fluoride int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
(35 reference statements)
4
20
0
1
Order By: Relevance
“…Intakes for girls per unit body weight during recent years of life (8.5–11 years) showed statistically significant, negative associations with several bone measures. Differences in effects of fluoride intakes on bone measures for girls versus boys were not seen previously in analyses of age 11 or 15 DXA‐determined BMC and BMD of the same cohort . This new finding could be due to the assessment of different bones, radius and tibia versus hip, spine, and whole body, or the use of pQCT in this study, which provided the opportunity to estimate cortical bone strength in vivo, as well as volumetric density .…”
Section: Discussionsupporting
confidence: 62%
“…Intakes for girls per unit body weight during recent years of life (8.5–11 years) showed statistically significant, negative associations with several bone measures. Differences in effects of fluoride intakes on bone measures for girls versus boys were not seen previously in analyses of age 11 or 15 DXA‐determined BMC and BMD of the same cohort . This new finding could be due to the assessment of different bones, radius and tibia versus hip, spine, and whole body, or the use of pQCT in this study, which provided the opportunity to estimate cortical bone strength in vivo, as well as volumetric density .…”
Section: Discussionsupporting
confidence: 62%
“…In children, intake of fluoridated water does not appear to affect bone density parameters through adolescence. [169] 4.4 Neurotoxicity/IQ effects…”
Section: Fracturesmentioning
confidence: 99%
“…In the Iowa Bone Development Study (IBDS), a longitudinal study investigating the effects of fluoride, other dietary factors, physical activity, lifestyle behaviours and genetic factors on bone development, Levy et al found no associations between period‐specific or cumulative (to 8.5 and 11 years) fluoride intakes and age 11 DXA of the hip, lumbar spine or whole body. In other analyses, Levy et al assessed the relationships between age 15 DXA bone measures and fluoride intake. No associations were observed for either sex, after controlling for calcium intake, physical activity and physical maturity, so the authors concluded that fluoride intake did not have a substantial impact on bone .…”
Section: Introductionmentioning
confidence: 99%
“…In other analyses, Levy et al assessed the relationships between age 15 DXA bone measures and fluoride intake. No associations were observed for either sex, after controlling for calcium intake, physical activity and physical maturity, so the authors concluded that fluoride intake did not have a substantial impact on bone . The majority of studies have used DXA scans to assess the bone characteristics, which are limited by the 2‐dimensional interpretation of a 3‐dimensional structure .…”
Section: Introductionmentioning
confidence: 99%